Analyzing Teacher’s Speech Acts in a Classroom-Based English Learning Video - Bindiya, Aisyah; Agustina, Sheila; Megawati, Fika; Novita, Dian; Mandarani, Vidya (Linguistics and ELT Journal, 2023)
This current research intends to identify and explain the forms of speech acts produced by the teacher in a learning video published on a YouTube channel. This research applies a qualitative descriptive method to respond to the problems studied. The findings indicate that among the various speech acts used, directive speech acts are more produced by the teacher in the video. It can be concluded from the results that 26 utterances produced by the teacher (25.2%) belong to representative speech acts, 52 utterances (50.5%) to directive speech acts, 2 utterances (2%) to commissive speech acts, 23 utterances (22.3%) to expressive speech acts. Directives are mostly produced by teachers inside the classroom while asking and questioning and become the most dominant directive speech acts produced by the teacher. It may happen because, in the learning video, the teacher gives students the opportunity to study a problem and try to solve the problem independently.